2004
DOI: 10.1021/ef0301452
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Oxygen Carriers for Chemical-Looping Combustion

Abstract: Chemical-looping combustion (CLC) has been suggested as an energetically efficient method for capture of carbon dioxide from the combustion of fuel gas. This technique involves the use of an oxygen carrier that transfers oxygen from the air to the fuel, preventing direct contact between them. The oxygen carrier is composed of a metal oxide as an oxygen source, and an inert as a binder for increasing the mechanical strength of the carrier. In this work, 240 samples composed of 40-80% of Cu, Fe, Mn, or Ni oxides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
498
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 680 publications
(507 citation statements)
references
References 12 publications
9
498
0
Order By: Relevance
“…The active metal oxides used in this study are nickel-, copper-, and iron-oxides, which have been widely suggested as the most promising OC candidates for CLC (e.g., nickel [20][21][22][23], copper [16,20,23,24], and iron [20,25,26]). Important physical and chemical properties of these metal oxides are summarized in Table 1.…”
Section: Oc Designmentioning
confidence: 99%
“…The active metal oxides used in this study are nickel-, copper-, and iron-oxides, which have been widely suggested as the most promising OC candidates for CLC (e.g., nickel [20][21][22][23], copper [16,20,23,24], and iron [20,25,26]). Important physical and chemical properties of these metal oxides are summarized in Table 1.…”
Section: Oc Designmentioning
confidence: 99%
“…Figure 2 shows the reactivity data obtained during the first redox cycle in the TGA with both oxygen carriers, NiO18-Al and NiO21-Al, at 1223 K using 15 vol. % of CH 4 , H 2 or CO as fuels. As can be seen, in the case of NiO18-Al, the reduction of the oxygen carrier particles proceeded in two stages.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…The major advantage of this process is that heat needed for converting CH 4 to H 2 is obtained without costly oxygen production and without mixing the air with carbon-containing fuel gases.…”
Section: Introductionmentioning
confidence: 99%
“…These oxygen carriers have shown adequate reactivity under atmospheric [10][11][12] and pressurized [13] conditions and high reactivity with CO and H 2 , and do not present thermodynamic limitations to fully convert CH 4 4 can be formed as a reduced compound and also achieve complete combustion of gas to CO 2 and H 2 O [14][15][16][17]. Thus, the oxygen transport capacity of the oxygen carrier is increased three times in comparison with the Fe 2 O 3 -Fe 3 O 4 redox couple.…”
Section: Introductionmentioning
confidence: 99%